Pengaruh Lingkungan Kerja Fisik dan Non Fisik Terhadap Kinerja Pegawai di Badan Pengelola Keuangan dan Aset Daerah Pemerintah Kabupaten Banyuasin - Puspita, Wiwik; Darwin, Darwin (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to investigate the relationship between physical work environment and non-physical work environment with employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Banyuasin Regency Government. This research method uses a quantitative approach through observation and questionnaires, with primary and secondary data sources. The total population of employees at the Regional Financial and Asset Management Agency (BPKAD) of Banyuasin Regency Government is 90 people. The sampling technique used is the NonProbability sampling technique with the saturated sample method. Data analysis was carried out using multiple linear regression analysis through the Statistical Program for Social Science (SPSS) version 29 tool. Various statistical tests were applied in this study, including validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, partial test, simultaneous test, and coefficient of determination test. From the results of the regression analysis, it can be concluded that the physical work environment variable has a significance level of Sig. t (0.000